Impact of completely histological remission on reducing flare-ups in moderate-to-severe, biologics-experienced ulcerative colitis patients with endoscopic remission - Zih-Hao Wei; Ren-Chin Wu; Chia-Jung Kuo; Horng-Yih Chiu; Pai-Jui Yeh; Chien-Ming Chen; Cheng-Tang Chiu; Yung-Kuan Tsou; Chen-Wang Chang; Yu-Bin Pan; Puo-Hsien Le (Journal of the Formosan Medical Association)
Background/purpose: Endoscopic remission is presently recognized as the standard therapeutic target in the treatment of ulcerative colitis (UC). However, achieving histological remission is increasingly viewed as a pivotal objective. This study investigates the effects of attaining completely histological remission on the clinical outcomes for UC patients with a high disease burden who have already reached endoscopic remission. This is the inaugural study to concentrate on this specific patient demographic. Methods: This retrospective cohort study enrolled moderate-to-severe, biologics-experienced UC patients with completely endoscopic remission (Mayo endoscopic subscore of 0) between June 2017 and October 2023 at Chang Gung Memorial Hospital, Linkou. Patients were classified into histological remission (HR) and non-histological remission (non-HR) groups based on the Nancy index (NI). HR was defined as an NI score of 0, with all other patients categorized as non-HR. The definition of flare-ups was based on both clinical and endoscopic evidence. Comparative analyses focused on baseline characteristics and clinical outcomes at follow-up. Results: A total of 42 patients (HR group: 23, non-HR group: 19) were included. The average follow-up duration was 17.6 months. Baseline characteristics were comparable between the groups. At the end of follow-up, the HR group showed a significantly lower rate of acute flare-ups (26.1% vs. 68.4%, P = 0.006). Although not statistically significant, the HR group also experienced fewer emergency department visits and hospital admissions. Conclusion: For moderate-to-severe, biologics-experienced UC patients in endoscopic remission, achieving completely histological remission is associated with a substantial reduction in flare-ups, suggesting its potential as a valuable therapeutic target.